Pemilihan Skala Prioritas Lokasi Pemasangan Sisip Trafo Distribusi dengan Metode Ahp – Topsis di PT. PLN ULP Pangkalan Bun - Bachtiar, Raditya Fahmi; Ratnasari, Vita (Syntax Corporation, 2023)
In this study, a total of 57 transformers with a load measurement status above 95% (overload) were recorded in the year 2022 and require transformer insertions. Every year, PLN ULP Pangkalan, on average, carries out a transformer insertion program of 10 transformers due to budget limitations. With this number, it is necessary to prioritize locations based on 6 criteria: transformers with overloads >95%, maneuvering up to 50% of existing transformers, a waiting list of ready-to-connect customers, business tariff (B) customers, landowner permits required, and the need for adding new network extensions. The Analytic Hierarchy Process (AHP) method is used for weighting the criteria, followed by the Technique for Other Preference by Similarity of Ideal Solution (TOPSIS) method to determine the priority sequence of distribution transformer insertion locations. The results of the AHP method show that the highest weight is assigned to the criteria of transformers with overloads >95%, with a weight of 59.3%. The lowest weight is assigned to the criteria of having business tariff (B) customers, with a weight of 3.8%. Using the TOPSIS method, the top priority location for distribution transformer insertion is at substation PBN-0262, with a preference value of 0.721038962870702. Meanwhile, the lowest priority location is found at transformer PBH-0054, with a preference value of 0.157302058325342. The sensitivity analysis results show that the priority sequence of distribution transformer insertion locations remains consistent and does not significantly change, indicating that the TOPSIS method's prioritization results in this study are consistent.